Study of Visual Quality and Higher Order Aberrations in Early Posterior Capsular Opacification - Zhangyi Li; Ji Sun; Bin Xv; Jiayv Zhang; Can Li (Journal of Ophthalmology)
Conclusions: Early PCO significantly impacts objective visual quality and HOAs in patients. Early intervention may provide greater visual benefits for patients implanted with MfIOL.